A New Xanthone from the Stems of Garcinia oligantha and their Anti-tobacco Mosaic Virus Activity - Meng, Yanlin; Yang, Yuchun; Qin, Ying; Xia, Congfang; Ye, Yanqing; Hu, Qiufen; Li, Yinke (Asian Journal of Chemistry, 2014)
For more bioactive compounds, phytochemical investigations of the methanol extract of the stems of Garcinia oligantha resulted in the isolation of a new xanthone, (S)-1,8-dihydroxy-4-(1-hydroxy-3-oxobutyl)-3-methoxy-9H-xanthen-9-one (1). Structural elucidation of 1 was performed by spectral methods. Compound 1 showed anti-tobacco mosaic virus (anti-TMV) activities with inhibition rates of 15.2 %.